Professor diretor de turma: um estudo entre Brasil e Portugal acerca de uma política educativa do estado do Ceará - Lima, Vagna Brito de (2017)
This paper presents the thesis report of the research carried out in the scope of the PhD in Education in the Postgraduate Program in Education (PPGE), Federal University of Paraíba (UFPB) − Brazil, whose objective was to analyze how the actors of the educational organization − managers, teachers, students and parents - appropriated the meanings of the position of teacher class director, in the context of the state school of Ceará, from 2011 to 2014. In the study, it was taken into account that the position of class director established in Ceará-Brazil is inspired by the homonymous post created in the Portuguese educational system in the 60's of the twentieth century. In this sense, the research carried out two case studies, one in the context of Ceará and the other in the north of Portugal. The educational policy, titled Project Teacher of the Class (PPDT), has been working in the Brazilian context precisely in the state schools of Ceará-Brazil since 2008, in the Portuguese educational system, the position is consolidated and regulated with the nomenclature, class director, since the end of 1968. In analyzing the continuities and ruptures of the Class Director to the Class Director, Sá (1997) highlights the "triple function" that unites the two positions, although with a different hierarchy of the functions in question. In the context of the analysis, the methodological approach was qualitative, the research strategy chosen was the single case study method (integrated and holistic), and the data collection instruments used were bibliographic and documentary research, questionnaire, observation non-participant and semi-structured interviews. The continuous policy cycle formulated by Richard Bowe, Stephen Ball and Anne Gold (1992) was adopted as the model of analysis; Ball (1994, 2011), articulating it with the school perspective as an educational organization of Licínio C. Lima (1998, 2001). Thus, the theoretical reference sought to articulate the approach of the policy cycle, with the contributions of the sociology of educational organizations, from the perspective of Ball (1992, 1994, 2002, 2004, 2011, 2013), Lima (1986, 1998, 2001), Sá (1997), and other contributions to the understanding of school as a complex educational organization. It is also worth mentioning that this work verified that the PPDT, in its trajectory, underwent the process of (re)interpretation and (re)contextualization, in the different contexts of the policy in action (influence context, text production context, practice context, context of results and effects and context of policy strategies). Effectively, the PPDT results from the "interpretation of the interpretation" on the class director existing in the Portuguese educational structure by the actors of interest groups in the Brazilian context. It is concluded that the actors for whom the PPDT policy is intended - students, parents, teachers and school administrators - are convinced of the importance of educational policy for the education of students in the school of Ceará, even if, above all, regarding the bureaucratic image of educational policy. Regarding the significations about the position/function of DT, the texts and speeches present significant approximations in the plane of the guidelines for action, although in the plane of action social, political and economic distances between the contexts investigated are observed.